Il ruolo degli spazi urbani nella carriera migratoria dei richiedenti asilo nella Città Metropolitana di Torino: una possibile tipologia - Mela, Alfredo; Novascone, Roberta (Fuori Luogo Journal of Sociology of Territory, Tourism, Technology, 2020)
This paper considers the concept of “career” by Becker (1973), adapted from Martiniello and Rea (2014) at migratory context. Development of interactions with the reception city and its spaces is a fundamental aspect of inclusion process. In this regard, which type of urban spaces can address individual resources and contribute to build personal strategies in order to develop migratory career? Which type of urban space allows a continuity between past and present? The case study is the Turin Metropolitan City, and the methodology is based on a campaign of in-depth interviews to different subjects as cultural mediators, psychologists, and asylum seekers. The goal is to build a taxonomy of urban spaces in order to answer to these questions.